Validity of four clinical prediction scores for pulmonary embolism in a sub-Saharan African setting: a protocol for a Cameroonian multicentre cross-sectional study - Joel Noutakdie Tochie; Agnès Esiéné; Paul Owono Etoundi; Junette Arlette Mbengono Metogo; Jacqueline Ze Minkande (BMJ Open)
Introduction Pulmonary embolism poses one of the most challenging diagnoses in medicine. Resolving these diagnostic difficulties is more crucial in emergency departments where fast and accurate decisions are needed for a life-saving purpose. Here, clinical pretest evaluation is an important step in the diagnostic algorithm of pulmonary embolism. Although clinical probability scores are widely used in emergency departments of sub-Saharan Africa, no study has cited their diagnostic performance in this resource-constrained environment. This study will seek to assess the performance of four routinely used clinical prediction models in Cameroonians presenting with suspicion of pulmonary embolism at the emergency department.Methods and analysis It will be a cross-sectional study comparing the sensitivity, specificity, positive and negative predictive values and accuracy of the Wells, Simplified Wells, Revised Geneva and the Simplified Revised Geneva Scores to CT pulmonary angiography as gold standard in all consecutive consenting patients aged above 15 years admitted for clinical suspicion of pulmonary embolism to the emergency departments of seven major referral hospitals of Cameroon between 1 July 2019 and 31 December 2020. The area under the receiver operating curve, calibration plots, Hosmer and Lemeshow statistics, observed/expected event rates, net benefit and decision curve will be measured of each the clinical prediction test to ascertain the clinical score with the best diagnostic performance.Ethics and dissemination Clearance has been obtained from the Institutional Review Board of the Faculty of medicine and biomedical sciences of the University of Yaounde I, Cameroon and the directorates of all participating hospitals to conduct this study. Also, informed consent will be sought from each patient or their legal next of kin and parents for minors, before enrolment into this study. The final study will be published in a peer-review journal and the findings presented to health authorities and healthcare providers.